2022
DOI: 10.3389/fendo.2021.802114
|View full text |Cite
|
Sign up to set email alerts
|

Novel Subgroups and Chronic Complications of Diabetes in Middle-Aged and Elderly Chinese:A Prospective Cohort Study

Abstract: BackgroundDiabetes mellitus, especially type 2 diabetes mellitus (T2DM), is regarded as highly heterogeneous. Novel diabetes phenotypes by cluster analysis have been proposed in Europeans but may show different cluster features in Asians. The applicability of cluster analysis in middle-aged and elderly Chinese community T2DM patients needs further investigation.MethodsParticipants were recruited from Jiading community in Shanghai, China. We adopted k-means cluster analysis in 1130 patients (aged ≥ 40 years) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(75 reference statements)
3
4
0
Order By: Relevance
“… 29 In another study including 80,224 patients who had obesity and 242,822 patients who did not have obesity, the cumulative incidence of severe liver disease at 10 years was <0.15%, <0.2%, and 0.4% in patients who were non-obese, overweight, and obese, respectively. 30 Despite a limited number of events, our results are in line with those of previous studies and suggest that SIRD patients should be carefully followed for liver-related complications. However, this interesting observation should be confirmed in other prospective cohorts with a longer follow-up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 29 In another study including 80,224 patients who had obesity and 242,822 patients who did not have obesity, the cumulative incidence of severe liver disease at 10 years was <0.15%, <0.2%, and 0.4% in patients who were non-obese, overweight, and obese, respectively. 30 Despite a limited number of events, our results are in line with those of previous studies and suggest that SIRD patients should be carefully followed for liver-related complications. However, this interesting observation should be confirmed in other prospective cohorts with a longer follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Two studies have evaluated hepatic fibrosis features among clusters using serum-based markers in a limited number of patients. 12 , 30 Here, we used liver biopsy and elastography to show that patients with SIRD had the highest risk for clinically significant fibrosis ( i.e. F2–F4).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the addictive impact of diabetes progression, patients with newly diagnosed T2DM were enrolled in our study. We found a high prevalence of MAFLD, which was comparable to the one among patients with recently diagnosed T2DM in Pakistan reported by Butt et al [32], but was higher than the ones reported in community-based studies [33,34]. But all the patients in our study were hospitalized and most of them were with high glycemic levels, which might suggest latent diabetes progression and might partly explained the discrepancy.…”
Section: Discussionsupporting
confidence: 62%
“…However, there are also differences. In our and other reported studies of East Asians including the Chinese (5,6,8,13), the BMI of the MOD cluster is generally lower than that of Caucasians (4, 7), which may be closely related to the dietary patterns of the different ethnic groups. The Chinese diet is characterized by a high intake of whole grains and vegetables, and a higher intake of fiber, thus reducing the risk of obesity (14).…”
Section: Discussionmentioning
confidence: 43%